Survey of husbandry and health on UK commercial dairy goat farms. (7th September 2019) - Anzuino, K.; Knowles, T. G.; Lee, M.R.F.; Grogono‐Thomas, R.
Abstract : Published research relevant to the UK dairy goat industry is scarce. Current practices and concerns within the UK dairy goat industry must be better understood if research is to have optimal value. A postal survey was conducted of the farmer membership of the Milking Goat Association as a first step in addressing gaps in knowledge. Questions were asked about husbandry practices, farmer observations of their goats and their priorities for further research. Seventy‐three per cent of Milking Goat Association members responded, representing 38 per cent of commercial dairy goat farms and 53 per cent of the commercial dairy goat population in England and Wales. Findings were comprehensive and showed extensive variation in farm practices. Farmers reported pneumonia and scours (diarrhoea) as the most prevalent illnesses of their kids. Pneumonia, diarrhoea, failure to conceive and poor growth were the most prevalent observations of youngstock. Overly fat body condition, assisted kidding, failure to conceive and difficulty drying off were the most prevalent observations of adult milking goats. Farmers' top priorities for further research were kid health (79.5 per cent of farmers), Johne's disease (69.5 per cent of farmers), tuberculosis (59 per cent of farmers) and nutrition (47.7 per cent of farmers).